Technological Advancements and Water Stress Reduction in Saudi Arabia: A Quantitative Analysis - Pawar, Puja Sunil; Sager, Laila Abd.; Alharbi, Ola; Aldawish, Aishah; ALanazi, Tawari (Journal of Ecohumanism, 2025)
This study examines the impact of digital economy indicators specifically, high-tech exports, ICT goods imports, and internet usage on natural resources, particularly water stress levels, in Saudi Arabia. It evaluates the relationship between digital adoption and water stress, exploring whether increased digital engagement promotes more efficient water use and conservation. Additionally, the study investigates how digital and technological advancements may indirectly contribute to water sustainability by improving public awareness, operational efficiency, and infrastructure development. The findings aim to inform strategies for sustainable water resource management in the context of Saudi Arabia’s digital transformation.